2014
DOI: 10.1177/1403494814523344
|View full text |Cite
|
Sign up to set email alerts
|

Who are the young adult Danish pre-drinkers, and why do they pre-drink before a night out?

Abstract: Not only young people's motives for pre-drinking but also the price of off- and on-premises alcohol should be considered for outlining prevention strategies seeking to reduce the alcohol quantities that young people pre-drink before a night out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Similarly, pre-loading behavior appears to be common to both males and females (DeJong, DeRicco, & Schneider, 2010;Hughes et al, 2008;Miller et al, 2013;Reed et al, 2011). However, recent studies show that males typically drink more during a pre-loading session than females (Foster & Ferguson, 2014;Miller et al, 2012;Østergaard & Andrade, 2014a), while others have suggested that pre-loading may lead women to drinking equivalent amounts to their male peers, or at least be at a greater risk of harm from this type of drinking (LaBrie & Pedersen, 2008;Merrill, Vermont, Bachrach, & Read, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Similarly, pre-loading behavior appears to be common to both males and females (DeJong, DeRicco, & Schneider, 2010;Hughes et al, 2008;Miller et al, 2013;Reed et al, 2011). However, recent studies show that males typically drink more during a pre-loading session than females (Foster & Ferguson, 2014;Miller et al, 2012;Østergaard & Andrade, 2014a), while others have suggested that pre-loading may lead women to drinking equivalent amounts to their male peers, or at least be at a greater risk of harm from this type of drinking (LaBrie & Pedersen, 2008;Merrill, Vermont, Bachrach, & Read, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%